2020
DOI: 10.1111/rda.13803
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a commercial intravaginal thermometer to predict calving in a Hungarian Holstein‐Friesian dairy farm

Abstract: Prediction of the exact time of calving would be highly important especially in small farms where there are no assistants working in day and night shifts. It has been known for a long time that precalving decrease in body temperature can be used for prediction of calving (Ewbank, 1963; Graf & Petersen, 1953; Porterfield & Olson, 1957). Since then, several reports have confirmed the precalving decrease in vaginal temperature by using sensors inserted into the vagina after attaching to a modified controlled inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Before calving, cows were fed a prepartum total mixed ration (TMR) twice daily at approximately 06:00 and 17:00 hr ad libitum containing a dietary forage‐to‐concentrate ratio of 78:22 on a dry matter (DM) basis as described previously (Choukeir et al., 2020 a,b). Water was available ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…Before calving, cows were fed a prepartum total mixed ration (TMR) twice daily at approximately 06:00 and 17:00 hr ad libitum containing a dietary forage‐to‐concentrate ratio of 78:22 on a dry matter (DM) basis as described previously (Choukeir et al., 2020 a,b). Water was available ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…The sensitivity of receiving the “possible calving in 48 h” SMS message was 40% [ 55 ], while the sensitivity of the “expected calving in 48 h” SMS message was 82.9%, respectively. In contrast, Choukeir et al [ 56 ] reported somewhat lower sensitivity results for possible and expected calvings in 48 h SMS messages (21.1% and 62.4%, respectively), while the positive predictive values of the SMS messages were 10.3% and 75%, respectively. Sakatani et al [ 57 ] used another temperature sensor that recorded the vaginal temperature.…”
Section: Prediction Of Calving By Measuring Body Temperature In Dairy...mentioning
confidence: 93%
“…To increase the accuracy of measuring the vaginal temperature, Ricci et al [ 63 ] have suggested using an intravaginal temperature of 38.2 °C as a cut-off value to predict calving within 24 h (vaginal temperature decreased from 38.65 °C to 38.12 °C between 48 and 60 h and 0 to 12 h before calving, respectively) because it can be more accurate (sensitivity: 86% vs. 66%) than a 0.21 °C decrease during the last 24 h before calving. Choukeir et al [ 56 ] found similar values in dairy cows because the mean temperature of 0 to 6 h before calving was 38.19 °C; however, this suggestion must be confirmed.…”
Section: Prediction Of Calving By Measuring Body Temperature In Dairy...mentioning
confidence: 95%
See 1 more Smart Citation
“…It is very time-consuming, costly and subjective to record the individual information of dairy cows by long-term manual observation. Currently, many researchers have used various sensors to detect the behavior of dairy cows [ 1 4 ]. Wearable sensors pose certain disadvantages that may cause stress responses in dairy cows.…”
Section: Introductionmentioning
confidence: 99%